(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Rapid restaining and reuse of archival slides for diagnostic and research purposes is impossible without decreasing the time spent on coverslip removal. Old archival slides can also be used in research, project, dissertation study, IHC, special staining or molecular study. Aim: The aim of the study is to analyse various methods of coverslip removal from the stored H&E stained slides and utilisation of the same for subsequent diagnosis of tumour subtypes using immunohistochemical analysis. Materials and methods: The archival slides were retrieved from the Department of Oral Pathology, Saveetha Dental College and Hospital. Samples were taken for 5 groups to analyse the duration for coverslip removal using xylene (RT), xylene (56°C), acetone, refrigerator - 18°C, Endo-frost. 10 H&E stained archival slides were taken in each group. Destaining and Immunohistochemical analysis was performed for a basic panel of 9 markers. Stained slides were graded by two independent observers. Good: Equal or superior intensity compared to positive control; Fair: Intensity graded lower compared to positive control; Poor: No adequate intensity and staining. SPSS v25 software was used for Statistical analysis. Descriptive analysis was done for various reagents time duration taken for coverslip removal. One way ANOVA was done to compare statistical significance between old archival H&E stained slides and newly sectioned slides. Results: In conventional xylene method (Room temperature), the mean time for removal of coverslip was 48 hour 30 minutes. Mean duration in which coverslip came-off was 5 minutes by Endo-frost minutes, 22 minutes by freezer -18°C method, 25 hours 50 minutes with xylene at 56°C and 56 hours with acetone method. One way ANOVA, post hoc Tukey HSD test showed significant results between groups (p<0.05). In our study, Pan CK, vimentin, SMA, S100, CD34 and CD45 showed good intensity; CD3 and CD20 showed fair intensity in old archival slides; Desmin showed poor intensity in old archival compared to newly sectioned slides Conclusion: Alternative methods especially freezing using Endofrost and refrigerator, xylene at high temperature and acetone method can be used for removal of coverslip. These methods are reliable within available resources for immunohistochemical analysis for research purposes.